Environmental characterization of the Ibaté municipality, SP – Brazil - Trevisan, Diego Peruchi; Santos, Bruna Felix dos; Melo, Naara Aline Tossani de; Moschini, Luiz Eduardo (Revista Hipótese, 2018)
The present study aims to perform the environmental characterization of the landscape in Ibaté-SP municipality, which involved the database elaboration with the information of road network, drainage network, hypsometry, slope, pedological units and use and land cover from 1990, 2000 and 2010. There have been modification processes of the landscape over the years, with the decrease of natural areas due to the expansion of agricultural activities that are driven by the characteristics present in the region, such as low slopes and the presence of soils, such as Ferralsols.
Keywords: Landscape characterization; Protection of natural resources; Use and land cover; Agricultural expansion